Чудеса света: полная энциклопедия / Наталья Петрова ; отв. ред. Л. Кондрашова - Петрова Наталья Николаевна (Эксмо, 2009)
Экземпляры: (20100611) / Инвентарный номер: 46030 / Цена: 486.09 / Сис.шифр: 26.89 я2ст. 46030 / Авт.знак: П 30 / ББК: 26.89 я2ст.